KONSERVASI LINGKUNGAN DI INDONESIA DALAM PERSPEKTIF FILSAFAT METAFISIKA - Dody Grace Febryanto Rongrean (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
This study is concerned with the current environmental crisis (deforestation, pollution, global warming, water pollution, plastic waste, and soil degradation). These phenomena occur as a result of the wrong perspective and relationship between humans and nature. Nature is often seen as merely existing as an instrument to fulfill human interests. This study aims to understand the relationship between humans and nature to deal with the environmental crisis that is occurring. The methodology used in this study is qualitative with a phenomenological approach because nature cannot be separated from human life, as a place to form experiences in daily life. Data were collected by reading literature related to the environmental crisis, and the data were analyzed with the theory of metaphysical philosophy. This study found that efforts to deal with the environmental crisis can begin with a good understanding of what nature is and its relationship with humans and God. It is concluded that nature is a harmony that must be preserved and cared for. In addition, in line with what Aristotle said, nature as reality exists to the extent that it exists and is not based on human ideas. The implication of environmental conservation is to build awareness that nature is an important part of human survival, which has value in itself, therefore humans should care for and preserve the harmony of nature.